Carboplatin Induction Chemotherapy in Clinically Lymph Node-positive Bladder Cancer - von Deimling, Markus; Mertens, Laura S; van Rhijn, Bas W G; Lotan, Yair; Spiess, Philippe E; Daneshmand, Siamak; Black, Peter C; Pallauf, Maximilian; D'Andrea, David; Moschini, Marco; Soria, Francesco; Del Giudice, Francesco; et al. (European urology open science, 2023)
BACKGROUND: There are currently no guideline recommendations regarding the treatment of cisplatin-ineligible, clinically lymph node-positive (cN+) bladder cancer (BCa). OBJECTIVE: To investigate the oncological efficacy of gemcitabine/carboplatin induction chemotherapy (IC) in comparison to cisplatin-based regimens in cN+ BCa. DESIGN SETTING AND PARTICIPANTS: This was an observational study of 369 patients with cT2-4 N1-3 M0 BCa. INTERVENTION: IC followed by consolidative radical cystectomy (RC). OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: The primary endpoints were the pathological objective response (pOR; ypT0/Ta/Tis/T1 N0) rate and the pathological complete response (pCR; ypT0N0) rate. We applied 3:1 propensity score matching (PSM) to reduce selection bias. Overall survival (OS) and cancer-specific survival (CSS) were compared across groups using the Kaplan-Meier method. Associations between the treatment regimen and survival endpoints were tested in multivariable Cox regression analyses. RESULTS AND LIMITATIONS: After PSM, a cohort of 216 patients was available for analysis, of whom 162 received cisplatin-based IC and 54 gemcitabine/carboplatin IC. At RC, 54 patients (25%) had a pOR and 36 (17%) had a pCR. The 2-yr CSS was 59.8% (95% confidence interval [CI] 51.9-69%) for patients who received cisplatin-based IC versus 38.8% (95% CI 26-57.9%) for those who received gemcitabine/carboplatin. For the pOR (p = 0.8), ypN0 status at RC (p = 0.5), and cN1 BCa subgroups (p = 0.7), there was no difference in CSS between cisplatin-based IC and gemcitabine/carboplatin. In the cN1 subgroup, treatment with gemcitabine/carboplatin was not associated with shorter OS (p = 0.2) or CSS (p = 0.1) on multivariable Cox regression analysis. CONCLUSIONS: Cisplatin-based IC seems to be superior to gemcitabine/carboplatin and should be the standard for cisplatin-eligible patients with cN+ BCa. Gemcitabine/carboplatin may be an alternative treatment for selected cisplatin-ineligible patients with cN+ BCa. In particular, selected cisplatin-ineligible patients with cN1 disease may benefit from gemcitabine/carboplatin IC. PATIENT SUMMARY: In this multicenter study, we found that selected patients with bladder cancer and clinical evidence of lymph node metastasis who cannot receive standard cisplatin-based chemotherapy before surgery to remove their bladder may benefit from chemotherapy with gemcitabine/carboplatin. Patients with a single lymph node metastasis may benefit the most.
Keywords: Survival; Urinary bladder neoplasms; Induction chemotherapy; Carboplatin; Oligometastatic